Healthy Eating for Elders: Drink to Your Health - Jennifer Hillan (EDIS, 2004)
Shakes and smoothies are a great and tasty way to incorporate more fruits and nutrients into your diet. For the recipes in this leaflet, blend all ingredients until smooth and creamy. If you use frozen fruit, no ice is needed. Otherwise, blend with a few ice cubes. Each recipe makes about 1–2 servings. Enjoy!